The social and economic integration of chinese immigrants in Portugal: generation 2.0 - Barata, Mariana Carvalho da Silva (2020)
With an increase of immigration waves from China to Portugal since the 1980’s, the more developed the Chinese community got, calling for research on the newer generations born in Portugal. The second-generation is typically more integrated in the host country in comparison to the first-generation. Chinese second-generation have citizenship, know the language, have access to education, employment and health care, and rarely partake in ethnic work. However, being a product of migration, these individuals can still experience a divided sense of identity. This research analyses the socio-economic and cultural integration of generation 2.0 Chinese individuals in Portugal, between the ages of 19 and 30 years old. To develop this research, semi-structured interviews to 15 individuals were conducted, addressing issues on family, educational and professional background, cultural identity and discrimination. Additionally, the most relevant obtained result shows a correlation between high levels of academic attainment and financial stability, and lower levels of integration in the future. It concludes that, to work towards integration, Portugal must adopt a multiculturalist society, while second-generation Chinese individuals could benefit from overcoming cultural barriers and improve their relationships with Portuguese natives. Nevertheless, Portugal’s lack of opportunities, low wages and discrimination occurrences, are the highest contributing factors for low rates of integration.